A colorimetric assay to detect mercury (II) ions in water sources using conjugated gold-nanoparticles - Busairi, Nurfatini Idayu (2018)
Rapid industrial progress has led to the elevation of heavy metal concentration in the environment, which raised tacit concerns. Among these metals, mercury (II) ion, Hg2+ is one of the most detrimental to the human health due to its neurotoxic and nephrotoxic properties. To date, methods to determine the presence of Hg2+ ions require expensive equipment and sophisticated operation. This is impractical for a constant monitoring of Hg2+ in water sources. Thus, it is necessary to develop a simple yet effective bio sensing method to monitor Hg2+ level in our environment. Recently, gold-nanoparticles (AuNPs) have attracted considerable amount of attention due to their nature of strong plasmonic resonance which can be exploited for a simple and rapid colorimetric assay. As the distance between nanoparticles decreases, the plasmon energy band is lowered and consequently it turns the colour of AuNPs from red to blue. The key of utilizing this phenomenon as a bio sensing mechanism is to control the AuNPs aggregation via surface chemistry approach. Here, a sensitive and practical colorimetric assay for in-situ detection of Hg2+ ions in water using cysteine functionalized gold nanoparticles (Cys- AuNPs) together with the addition of polyamidoamine (PAMAM), G2 dendrimer is reported. In this study, Cys-AuNPs and PAMAM dendrimer specifically capture Hg2+ ions and induce colour changes of the solution. The mechanism of Hg2+ interaction with the system was investigated using UV-vis spectrophotometer, dynamic light scattering (DLS) and transmission electron microscope (TEM). To increase the practicality value of the system, a custom-made chamber to be integrated with a mobile phone was fabricated. Colour changes can be monitored using a mobile app. The newly developed detection system can detect Hg2+ as low as 0.5 part per billion (ppb) in a laboratory prepared sample or in a real river water sample. The results were validated using direct thermal decomposition mercury analyser. This cost-effective colorimetric approach is practical to determine the presence of Hg2+ water sources.